Metaverso Architettura e Territorio. L’esperienza del SicilyLab2022 a Gioiosa Marea - De Francesco, Gaetano; Falcone, Michela (Archeomatica, 2023)
The project works on a physical and a virtual dimension. The question designers are asking is how to use digital technology to break down barriers, be they physical, psychological or cultural. What is imagined is a virtual twin of the cave, an entity that can exist in the Metaverse – hence the nickname Meta-Tone – and be accessible in a new way. The project involves the creation of an immersive virtual environment that reconstructs the cave in a simplified way and in which the user is able to navigate through Oculus technology. Virtual reality will be used to attract the user and make him curious about the underground cavity.